2003
DOI: 10.1093/qjmed/hcg077
|View full text |Cite
|
Sign up to set email alerts
|

Severe P. falciparum malaria in Kenyan children: evidence for hypovolaemia

Abstract: Impaired tissue perfusion may play a role in the mortality of severe malaria. Moreover, volume resuscitation, an important life-saving intervention in children with hypovolaemia, should be considered in severe malaria with evidence of impaired tissue perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 24 publications
5
97
1
1
Order By: Relevance
“…13 Of our patients, 26% had bacteraemia and 55.2% of those who died had bacteraemia. Hence, in Africa, where bacterial infections such as staphylococcal and Salmonella infections are prevalent, 14 the use of antibiotics for severely anaemic children may be justified, especially where blood culture facilities are not readily available. Our study found that hypotension predicted death among the children with severe anaemia, consistent with Maitland et al…”
Section: Discussionmentioning
confidence: 99%
“…13 Of our patients, 26% had bacteraemia and 55.2% of those who died had bacteraemia. Hence, in Africa, where bacterial infections such as staphylococcal and Salmonella infections are prevalent, 14 the use of antibiotics for severely anaemic children may be justified, especially where blood culture facilities are not readily available. Our study found that hypotension predicted death among the children with severe anaemia, consistent with Maitland et al…”
Section: Discussionmentioning
confidence: 99%
“…For children developing severe and complicated Plasmodium falciparum malaria case fatality on current treatment remains high [1]. Amongst the physiological derangements associated with severe, life-threatening malaria, metabolic acidosis has emerged as a central feature, being widely recognised as the best independent predictor of death in both children and adults [2][3][4][5].The highest mortality occurs in children presenting in deep coma with metabolic acidosis [6,7]. We have previously hypothesised that acidosis in severe malaria is due in part to impaired perfusion (or hypovolaemia) [3,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…More so, conducting a clinical trial of this nature would be unethical. Previous studies have reported prevalence ranging from 2.9% to 17% [10][11][12][13][14] . All these studies were not focused on the role of oxygen saturation in malarial-related deaths.…”
mentioning
confidence: 99%